how do i solve (e^x + e^-x)/ (e^x - e^-x) ln(log(x)) = 0 sqrt(ln x) = ln sqrt(x) (log3X)^2 - log3X^2 = 3 ln x^2 = (lnx)^2 5^(2x) - 3(5^x) +2 = 0 ln x ^(lnx) = 4
Follow Math Help Forum on Facebook and Google+
this one is just an expression did you mean to set to zero otherwise all one can is just come up with an alternate form
Last edited by bigwave; Dec 13th 2009 at 11:19 PM. Reason: latex
1) The equation can be written as Square both members: Now continue. 2) Let and solve the quadratic. 3) 4) Let and solve the quadratic. 5)
Hello, cheezeandbunnies! Here's some help . . . . . . . not an equation We have: . Therefore: . We have: . Square both sides: . Factor: . Therefore: . We have: . Factor: . Therefore: .
View Tag Cloud